Residential vulnerability and the housing question: a social and spatial-oriented analysis for the Andalusia metropolitan areas - Andrea Andújar Llosa (Boletín de la Asociación de Geógrafos Españoles)
The mismatch between basic household needs and the conditions and characteristics of dwellings is at the centre of residential vulnerability. According to the guidelines established in the international and national level, this paper aims to apply a two-dimensional perspective in urban and housing research. Indeed, the concept of residential vulnerability is used to address, jointly, the areas and social groups at risk due to housing characteristics and conditions. By analysing 2011 Population and Housing Census data, three indicators were developed, linking physical housing conditions to relevant social dimensions. This integrated perspective is used to identify the size and range of residential vulnerability situations brought about by the physical characteristics of dwellings and how they link to relevant social dimensions in the Andalusia metropolitan system. Results revealed significant deficiencies in housing conditions, yielding different impacts by metropolitan area and social group. Although the reported problems did not affect a sizeable proportion of the population, they proved relevant given the severity of the issues addressed and the social groups involved. These shortcomings should constitute a priority for sustainable housing policies and urban plans.